Ecological and Human Dimensions of the Monk Parakeet Damage to Crops in Argentina - Canavelli, Sonia Beatriz (University of Florida, 2020)
Tesis para obtener el grado de Doctor of Philosophy, de la University of Florida (Estados Unidos), en 2011